Constitutional principles of technical creation regulation - Пономаренко, Олександр Васильович; Борисова, К. С. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article investigates issues of current state of legal regulation and technical creativity. The authors examines the issues of inventive activity and provides the ways to improve the system the legal protection of inventions.